2009
DOI: 10.1158/1078-0432.ccr-09-0856
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Fatty Acid Synthase with Anticancer Activity

Abstract: Purpose: Fatty acid synthase (FASN) is overexpressed in human breast carcinoma.The natural polyphenol (-)-epigallocatechin-3-gallate blocks in vitro FASN activity and leads to apoptosis in breast cancer cells without any effects on carnitine palmitoyltransferase-1 (CPT-1) activity, and in vivo, does not decrease body weight. We synthesized a panel of new polyphenolic compounds and tested their effects on breast cancer models. Experimental Design: We evaluated the in vitro effects of the compounds on breast can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 29 publications
4
103
0
1
Order By: Relevance
“…Fatty acid synthase (FASN) showed activity in promoting tumorigenesis by activating HER2/PI3K/AKT/mTOR and MAPK signaling pathways (93)(94)(95). EGFR and pEGFR increased in trastuzumab resistant cells noticeably, which was consistent with the study of Wu et al (92).…”
Section: Her2 Tk Inhibitorssupporting
confidence: 88%
“…Fatty acid synthase (FASN) showed activity in promoting tumorigenesis by activating HER2/PI3K/AKT/mTOR and MAPK signaling pathways (93)(94)(95). EGFR and pEGFR increased in trastuzumab resistant cells noticeably, which was consistent with the study of Wu et al (92).…”
Section: Her2 Tk Inhibitorssupporting
confidence: 88%
“…A previous study demonstrated that small interfering RNA silencing of FASN decreased the PI3K/Akt/NF-κB signaling pathway in vitro (32); however, the mechanism (s) responsible for the inhibition of Akt activity due to the downregula tion of FASN have not been investigated. A study by Puig et al (35) revealed that inhibition of FASN resulted in a marked decrease in the active forms of the HER2 protein. FASN-mediated lipogenesis produces phospholipids that are incorporated into cell membranes and partitioned into lipid rafts, which accommodate HER proteins and form signaling platforms.…”
Section: Discussionmentioning
confidence: 99%
“…The FASN inhibitory drug C75 has been described as a malonyl-CoA analogue and is known to concomitantly activate fatty acid degradation by antagonizing the allosteric inhibitory effect of malonyl-CoA on carnitine palmitoyltransferase-I (CPT-I), the major rate-limiting enzyme for long-chain fatty acid oxidation (18)(19)(20). Therefore, we examined whether the observed C75-induced effects on PI3K downstream protein expression, phosphorylation, and stability were indeed because of blockade of FASN and not because of concurrent activation of CPT-I by transiently transfecting A2780 cells with a set of 4 different FASNspecific siRNAs.…”
Section: C75 Stimulates Protein Ubiquitinationmentioning
confidence: 99%